THE INFLUENCE OF EXTERNAL AND INTERNAL FACTORS ON ORGANIZATIONAL DESIGN CHOICE: A CASE STUDY OF STATE-OWNED ENTERPRISES (BUMN) - Mohammad Anwar Gani; Afrizon Afrizon; Rizki Juliandika (Taksasila Edukasi Insani, 2025)
The 21st century is characterized by deep uncertainty, high volatility, rampant complexity, and unavoidable ambiguity, commonly known as the VUCA era. In this dynamic landscape, organizations, particularly State-Owned Enterprises (BUMN), face intense pressure to adapt, innovate, and strategically respond to survive and thrive. Organizational design, extending beyond mere hierarchical charting, is a critical strategic process that profoundly impacts operational efficiency, work culture, employee motivation, and long-term objectives. This study adopts a qualitative phenomenological approach, based on an intensive literature review, to explore the lived experiences of BUMN leaders in navigating these complex external (e.g., market dynamics, technological disruption, government regulations) and internal (e.g., organizational strategy, culture, resources) factors to inform their organizational design choices. The research aims to understand how leaders interpret and mediate these pressures, contributing to organizational theory and offering practical insights for BUMNs in fostering resilient, adaptive, and human-centric organizations.Keywords: BUMN, External Factors, Internal Factors, Organizational Design, Strategic Leadership